Support group model for Vietnamese people affected by substance abuse and HIV/AIDS - Nguyen, Loan Hoi; Bui, Minh Thanh; Nguyen, Trang Thu (International Journal of Public Health Science (IJPHS), 2025)
As commonly seen in East and Southeast Asia, one of the major responses of the Vietnamese government to substance abuse is compulsory drug rehabilitation, which was found not very effective with a high relapse rate. Since 2000s, many people affected by substance abuse (PASA) in Vietnam started actively seeking help from group models in Buddhist temples for their substance abuse and HIV/AIDS problems. This case study aimed to examine the philosophical foundation, theoretical mechanism, implementation, and tentative outcomes of the group work model with the PASA at a Buddhist temple in the North of Vietnam. This qualitative approach study collected data from participation observation, reports collected from the temple, and 14 in-depth interviews with two monks, two rehabilitation therapists, and 10 PASA, mostly narcotic addicts, who participated in the group model in the temple. Results of the study show that PASA were self-motivated to voluntarily participate and maintain their membership in the group model. The head monk/master and his fellow monks played the role of the para-interventionists to provide comprehensive care for PASA members using Buddhist core values and philosophy in its approach. Both the para-interventionists and group members perceived their relationship with each other as equal, respectful, supportive, and therapeutic. The results provide implications for the development of new intervention models that are culturally appropriate in the unique sociocultural context of Vietnam and other countries that shared similar religious influences.